2014
DOI: 10.1371/journal.pone.0089443
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Modulates Effective Connectivity between Cortex and Striatum

Abstract: It has been notoriously difficult to understand interactions in the basal ganglia because of multiple recurrent loops. Another complication is that activity there is strongly dependent on behavior, suggesting that directional interactions, or effective connections, can dynamically change. A simplifying approach would be to examine just the direct, monosynaptic projections from cortex to striatum and contrast this with the polysynaptic feedback connections from striatum to cortex. Previous work by others on eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…5C). Furthermore, coupling in the opposite direction (i.e., striatal unit activity and cortical LFP signal) showed a weaker response, demonstrating that interregional synchronization preferentially occurs from the cortex to striatum (Nakhnikian et al 2014), consistent with corticostriatal wiring. To further elucidate the spectral properties of this oscillatory coupling, we calculated the spike-LFP coherence in the resting state and found that the strongest frequency mode indeed occurred in the delta band (mean Ϯ SD: 2.8 Ϯ 0.5 Hz; Fig.…”
Section: Recording System Demonstrationmentioning
confidence: 76%
“…5C). Furthermore, coupling in the opposite direction (i.e., striatal unit activity and cortical LFP signal) showed a weaker response, demonstrating that interregional synchronization preferentially occurs from the cortex to striatum (Nakhnikian et al 2014), consistent with corticostriatal wiring. To further elucidate the spectral properties of this oscillatory coupling, we calculated the spike-LFP coherence in the resting state and found that the strongest frequency mode indeed occurred in the delta band (mean Ϯ SD: 2.8 Ϯ 0.5 Hz; Fig.…”
Section: Recording System Demonstrationmentioning
confidence: 76%
“…However, cross-correlation is model dependent, unlike transfer entropy. Granger causality has been widely used to assess causal interactions between both continuous and discrete neural signals (Granger, 1969; Ding et al, 2006; Nakhnikian et al, 2014), though underlying assumptions about the analysis (e.g., Gaussian distributed data) must be thoroughly evaluated. Additionally, neural encoding is frequently assessed by applying statistical tests to neural signal observations under two conditions (e.g., stimulus on versus off or behavior A versus B).…”
Section: Discussionmentioning
confidence: 99%
“…In these models discrete cellular connectivity in terms of inputs and outputs are used to infer not only elongation of neurites, but unidirectional control over axonal connectivity. 119,120 Whilst grooves and channels orient process growth, it is a linear orientation with no directional selectivity, the neuronal processes grow from one chamber to the adjacent chamber and vice versa. 114 In order to direct neural process growth in a single direction only, it is necessary to further optimise the design of the micro-channels between chambers.…”
Section: Directing Neuritesmentioning
confidence: 99%